Role of Dietary Pattern on the Microbial Diversity in the Gut of the Experimental Mice - Samuel, Rosa J.; Joy, Omana; Piruthiviraj, Prakash; Kaliannan, Thamaraiselvi (Asian Journal of Engineering and Applied Technology, 2018)
Animal models are important for biomedical research as they help us to understand the mechanisms and functions similar to humans. Microbiological analysis is an integral part of animal studies especially when looking for gut microbiota changes. Several factors such as diet, antibiotics etc. have an impact on the composition of the gut. While many conventional and molecular methods are used for the identification of microbiota, this study aimed at evaluating the usefulness of flow cytometry for identification of bacteria based on their ability to scatter light. Fresh gut samples from mice were collected and cultured on nutrient agar followed by plating on selective media. The isolates were characterized and differentiated by biochemical tests and FACS (fluorescent activated cell sorter) analysis. The major group of isolates obtained from culture methods and biochemical characterization were identified as Proteus and Klebsiella species. Forward and side scatter analysis of the samples showed two distinct patterns in the plots and correlated with the microbiological results. From the results it was found that flow cytometry can be effectively used as method of rapid detection of microorganisms from animal samples.